Cinética ruminal de ovinos alimentados com bagaço do pseudofruto do caju desidratado em substituição a silagem de sorgo - Lopes, Kátia Tatiana de Lima (Universidade Federal Rural do Semi-Árido, 2014)
The objective was to evaluate the ruminal degradability of dry matter, and physicochemical parameters of the rumen fluid of sheep fed with bagasse pseudofruit cashew dehydrated replacing sorghum silage. Were used four crossbred sheep of Santa Inês x Morada Nova, fistulated in the rumen with na average weight of 30 ± 0.5 kg. Experimental tests were composed of four treatments, representing increasing levels of substitution of (BPCD) in sorghum silage, consisting of the levels of 0%, 8%, 16% and 24%, based on natural matter. We evaluated the potential degradability (PD) and effective (ED) of dry matter and the physical and chemical characteristics of rumen fluid (pH, temperature, ammonia nitrogen, methylene blue reduction time, flotation and sedimentation time, color, smell and consistency). The experimental design was a Latin square 4x4, with four substitution levels and four collection periods of rumen fluid after feeding, and the data submitted to analysis of variance and regression testing. The pH did not differ between treatments (P> 0.05). The temperature there was no significant difference (P> 0.05) on the basis of replacement levels of assessed BPCD, however, differed in terms of collection times. The ammonia nitrogen (NH3-N) presented significant difference (P <0.05); (P <0.01) according to the replacement levels BPCD and the rumen fluid sampling times after feeding. The methylene blue reduction time and flotation and sedimentation time significant differences (P <0.05); (P <0.01). The physical characteristics of rumen fluid were within the normal patterns. The potential degradability of dry matter with the addition of 24% of the cashew bagasse, has obtained value near of sorghum silage with 0% of cashew bagasse. The effective degradability of dry matter increased with the addition of BPCD, reaching higher values in the level of 24%. Results showed that the substitution of bagasse pseudofruit cashew dehydrated in sorghum silage did not affect the rumen environment, with potential degradability of dry matter silage next to the pure and higher effective degradability and can be used in up to 24% in diets for sheep
Ruminal kinetic of sheep fed with bagasse pseudofruit cashew dehydrated substitution sorghum silage
Keywords: Degradabilidade; Matéria seca; Ovinos; Parâmetros ruminais; Degradability; Dry matter; Sheeps; Ruminal parameters; CIENCIAS AGRARIAS::MEDICINA VETERINARIA